Mikroenkapsulasi Parasetamol Dengan Metode Penguapan Pelarut Menggunakan Polimer Natrium Karboksimetil (NaCMC) - Auzal Halim; Oktavia Arianti; Salman Umar (STIFARM Padang, 2011)
Has been researched about microencapsulation of paracetamol with solvent evaporation method using polymer sodium carboxymetil cellulose (NaCMC). Determination of paracetamol level carried out by UV Spectrophotometer at a wavelength of 243,5 nm, the dissolution test using solution phosphate buffer with pH 5,8 and the method used is Metoda Dayung. From the research result, obtained dissolution rate microcapsules of paracetamol on formula 1 is higher than formula 2 and 3. This is because in formula 2 and formula 3 show the addition of coating as a microcapsule wall – forming wich will reduce the speed of drug release. Model kinetics of active ingredient release from microcapsules of paracetamol following the zero order and first order.